2013
DOI: 10.1111/1462-2920.12313
|View full text |Cite
|
Sign up to set email alerts
|

Life with compass: diversity and biogeography of magnetotactic bacteria

Abstract: SummaryMagnetotactic bacteria (MTB) are unique in their ability to synthesize intracellular nano-sized minerals of magnetite and/or greigite magnetosomes for magnetic orientation. Thus, they provide an excellent model system to investigate mechanisms of biomineralization. MTB play important roles in bulk sedimentary magnetism and have numerous versatile applications in paleoenvironmental reconstructions, and biotechnological and biomedical fields. Significant progress has been made in recent years in describin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
98
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 107 publications
(102 citation statements)
references
References 95 publications
2
98
0
2
Order By: Relevance
“…However, recent cultivation-independent analyses have revealed an unexpected diversity of MTB outside Proteobacteria (Kolinko et al, 2012;Lefèvre and Bazylinski, 2013;Lin et al, 2014). Among them, those belonging to the genus 'Candidatus Magnetobacterium' in the phylum Nitrospirae are of great interest (Garrity and Holt, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, recent cultivation-independent analyses have revealed an unexpected diversity of MTB outside Proteobacteria (Kolinko et al, 2012;Lefèvre and Bazylinski, 2013;Lin et al, 2014). Among them, those belonging to the genus 'Candidatus Magnetobacterium' in the phylum Nitrospirae are of great interest (Garrity and Holt, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…Members of this genus, such as 'Candidatus M. bavaricum' (henceforth referred to as Mbav), have giant cell sizes (6-10 mm) and are capable of forming as many as 1000 bullet-shaped magnetite magnetosomes arranged into multiple bundles of chains in a single cell, which is different from Proteobacteria MTB (Spring et al, 1993). Originally discovered through electron microscope observation and ribosomal RNA gene sequencing (Vali et al, 1987;Spring et al, 1993), the Nitrospirae MTB are found to be widespread in aquatic environments and sometimes even account for a significant proportion (up to 30%) of microbial biomass in the microhabitats (Spring et al, 1993;Lin et al, 2014). Recent studies have suggested that these organisms may be capable of oxidizing sulfur (Spring and Bazylinski, 2006;Jogler et al, 2010), thus linking this genus to the key steps of iron and sulfur cycles in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetosomes are normally organized into chain-like structures to facilitate the navigation of MTB using Earth's magnetic field, a behavior known as magnetotaxis (2). Because of their ubiquitous distribution, MTB play key roles in global iron, nitrogen, sulfur, and carbon cycling (3). Magnetosome crystals can be preserved as magnetofossils after MTB die and lyse, and these crystals can be used as reliable biomarkers and are major contributors to sedimentary paleomagnetic records (4)(5)(6)(7).…”
mentioning
confidence: 99%
“…The crystal sizes and shapes are highly regulated, and Ͼ10 magnetosomes typically align along the cell's long axis (8)(9)(10). Thus, the formation of magnetosomes confers a magnetic moment to the cells and allows them to migrate along oxygen gradients in an aquatic environment under the influence of the Earth's geomagnetic field (7).…”
mentioning
confidence: 99%